A molecular dynamics simulation study of sucking a single polymer chain into nanopores: blockage and memory effects. Issue 8 (7th May 2015) - Li, Ziqi; Guo, Hongxia
<x xml:space="preserve">Abstract</x> The scaling exponent of translocation time changes from 1.19 to 1.37 and memory effect cluster size changes from 6–8 to 4 beads when the flux strength is enhanced.